Slightly Generalized $β$-Continuous Functions - Arora, S. C.; Tahiliani, Sanjay (Sarajevo Journal of Mathematics, 2024)
A new class of functions, called slightly generalized $β$-continuous functions is introduced. Basic properties of slightly generalized $β$-continuous functions are studied. The class of slightly generalized $β$-continuous functions properly includes the class of slightly $β$-continuous functions and generalized $β$-continuous functions. Also, by using slightly generalized $β$-continuous functions, some properties of domain/range of functions are characterized. 2010 Mathematics Subject Classification. 54C08